Camp Manual of the Spanish Youth Front (Frente de Juventudes), editions of 1943 and 1948: variations around the political culture and the discipline of the bodies in Franco’s Spain - Castillejo Cambra, Emilio (Historia y Memoria de la Educación, 2020)
This article analyzes and compares the 1943 and 1948 editions of the Camp Manual, which provides instructions for the camp commanders of the Youth Front, the Francoist equivalent of Mussolini’s Balilla and the Nazi Hitler-Jugend. In these manuals, the camp appears as a microcosm that reflects the organic structure and government practice of the Francoist State, including its biopolitical aspects: health, food storage, calorie consumption... The political culture that they transmit and its variants maintain an affinity with the normalization of the bodies of the campers: while the Phalangist subculture imposes strength, martiality and rectitude upon the bodies, the Catholic subculture imposes meekness and sinuous forms. The two editions of the manual also reflect the evolution of Franco’s regime. In the 1943 edition, the leaflet of the camp leader reflects the Fascistization of the State. The 1948 edition, on the other hand, stresses the legitimization of the encyclical Divini Illius Magistri or the imposition of a Christian pedagogy (principle of self-direction), and it speaks of the establishment of a Catholic State. This includes the concept of the culture of the participative subject, linked in turn to a new normalization of the bodies (greater distention, oblique lines), without this implying the disappearance of the traditional forms of control or the automatic movements (parades, formations), characteristic of the culture of the subject that gives unity to Francoism.